Metabolic responses to prolonged work during treadmill and water immersion running - Frangolias, D. D.; Rhodes, E. C.; Taunton, J. E.; Belcastro, A. N.; Coutts, K. D. (Journal of Science and Medicine in Sport, 2000)
The primary aim of this study was to compare the physiological responses to prolonged treadmill (TM) and water immersion to the neck (WI) running at threshold intensity. Ten endurance runners performed TM and WI running VO2max tests. Subjects completed submaximal performance tests at ventilatory threshold (Tvent) intensities under TM and WI conditions and responses at 15 and 42 minutes examined. VO2 was lower in WI (p<0.05) at maximal effort and Tvent. The Tvent VO2 intensities interpolated from the TM and WI VO2max tests were performed in both TM (i.e., TM@TM(tvent),TM@WI(tvent), corresponding to 77.6 and 71.3% respectively of TM VO2max) and WI conditions (i.e., WI@TM(tvent), WI@WI(tvent), corresponding to 85.5% and 78.2% respectively of WI VO2max). Each of the dependent variables was analyzed using a 3-way repeated measures ANOVA (2 conditions X 2 exercise intensities X 7 time points during exercise). VO2max values were significantly lower in the WI (52.4(5.1) ml.kg(-1) min(-1)) versus TM (59.7(6.5) ml.kg(-1) min(-1)) condition. VO2 during submaximal tests were similar during the TM and WI conditions. HR and [BLa] responses to exercise at and above WI(tvent) were similar during short-term exercise, but values tended to be lower during prolonged exercise in the WI condition. There were no statistical differences in VE responses in the 2 conditions, however as with HR and [BLa] an upward trend was noted with TM exercise over the 42 minute duration of the tests. RPE at WI(tvent) was similar for TM and WI exercise sessions, however, RPE at TM(tvent) was higher during WI compared to TM running. Cardiovascular drift was observed during prolonged TM but not WI running. Results suggest differences in metabolic responses to prolonged submaximal exercise in WI, however it can be used effectively for cross training.